Drug-induced priapism. (June 2020) - Pucci, Mark; Roussak, Penelope; Pang, David; Darrad, Maitrey
Abstract : Summary: Drug-induced priapism is a rare but serious condition associated with a variety of prescribed and illicit drugs. The most common causes include antipsychotics, oral phosphodiesterase type 5 inhibitors, the antidepressant trazodone, and alpha-adrenoceptor antagonists prescribed for hypertension or lower urinary tract symptoms (such as prazosin and tamsulosin). Risk factors include predisposing conditions such as sickle cell disease, spinal cord injury, and history of previous priapism. When patients present to the Emergency Department with priapism, a thorough drug history should be carried out, including use of recreational drugs and drugs obtained without prescription.